COUNSELING ON FEED RATIONERING AND ANIMAL HEALTH TRAINING TO INCREASE LIVESTOCK PRODUCTION IN MALIKU DISTRICT, PULANG PISAU REGENCY, CENTRAL KALIMANTAN - Nanik Hidayatik; Herry Agoes Hermadi; Mirni Lamid; Sunaryo Hadi Warsito (Universitas Airlangga, 2023)
The Community Service carried out in Pulang Pisau Regency in 2022 aims to help increase the livestock population. This activity was conducted in July - August 2022, through the preparation stage, the implementation of activities consisting of counselling and field activities, as well as evaluation activities with participants filling out questionnaires. The material presented was FMD and its handling, production duck and ruminant rations, as well as cattle management and increasing livestock production. Based on the questionnaire results, in general, it was found that participants knowledge and understanding of the materials presented were increased.